Buying online: Sequential decision making by shopbot visitors - Uwe Dulleck; Franz Hackl; Bernhard Weiss; Rudolf Winter-Ebmer (Institute for Advanced Studies (IHS), 2008)
In this article we propose a two stage procedure to model demand decisions by customers who are balancing several dimensions of a product. We then test our procedure by analyzing the behavior of buyers from an Austrian price comparison site. Although in such a market a consumer will typically search for the cheapest price for a given product, reliability and service of the supplier are other important characteristics of a retailer. In our data, consumers follow such a two stage procedure: they select a shortlist of suppliers by using the price variable only; finally, they trade off reliability and price among these shortlisted suppliers.
Keywords: L81; D83; 330; e-commerce; price comparison; decision theory; heuristics; seller reputation; Online-Handel; Internetportal; Preis; Informationsversorgung; Konsumentenverhalten; Entscheidungstheorie